Prevalence, risk factors and consequences of newborns born small for gestational age: a multisite study in Nepal - Shyam Sundar Budhathoki; Ashish KC; Rejina Gurung; Prajwal Paudel; Honey Malla; Pragya Gautam Paudel; Avinash K Sunny; Abhishek Gurung; Navraj KC (BMJ Publishing Group, 2020)
Objective To identify the prevalence, risk factors and health impacts associated with small for gestational age (SGA) births in Nepal.Methods A cross-sectional study was conducted in 12 public hospitals in Nepal from 1 July 2017 to 29 August 2018. A total of 60 695 babies delivered in these hospitals during the study period were eligible for inclusion. Clinical information of mothers and newborns was collected by data collectors using a data retrieval form. A semistructured interview was conducted at the time of discharge to gather sociodemographic information from women who provided the consent (n=50 392). Babies weighing less than the 10th percentile for their gestational age were classified as SGA. Demographic, obstetric and neonatal characteristics of study participants were analysed for associations with SGA. The association between SGA and likelihood of babies requiring resuscitation or resulting in stillbirth and neonatal death was also explored.Results The prevalence of SGA births across the 12 hospitals observed in Nepal was 11.9%. After multiple variable adjustment, several factors were found to be associated with SGA births, including whether mothers were illiterate compared with those completing secondary and higher education (adjusted OR (AOR)=1.73; 95% CI 1.09 to 2.76), use of polluted fuel compared with use of clean fuel for cooking (AOR=1.51; 95% CI 1.16 to 1.97), first antenatal care (ANC) visit occurring during the third trimester compared with first trimester (AOR=1.82; 95% CI 1.27 to 2.61) and multiple deliveries compared with single delivery (AOR=3.07; 95% CI 1.46 to 6.46). SGA was significantly associated with stillbirth (AOR=7.30; 95% CI 6.26 to 8.52) and neonatal mortality (AOR=5.34; 95% CI 4.65 to 6.12).Conclusions Low literacy status of mothers, use of polluted fuel for cooking, time of first ANC visit and multiple deliveries are associated with SGA births. Interventions encouraging pregnant women to attend ANC visits early can reduce the burden of SGA births.